ANAEROBIC FERMENTATION OF RICE BRAN WITH STARTER LIQUID ORGANIC SUPPLEMENT (LOS) FROM GOAT FECES - C. S., DEVIARY; HERNAMAN, I.; AYUNINGSIH, B.; ROSANI, U. (Majalah Ilmiah Peternakan, 2025)
The research was conducted with the aim of determining the effect of using Liquid Organic Supplement (LOS) derived from goat feces on the quality of fermented rice bran. The materials used were rice bran and the feces of Saanen dairy goats. The research employed an experimental method and a completely randomized design (CRD) with 3 treatments and 6 replications. The treatments consisted of P0 (1 kilogram of rice bran: 300 grams of molas- ses), P1 (1 kilogram of rice bran: 200 grams of molasses: 100 milliliters of LOS), and P2 (1 kilogram of rice bran: 100 grams of molasses: 200 milliliters of LOS). The variables investigated were lactic acid content, pH, dry matter loss, and Fleigh value. The data were analyzed using Analysis of Variance (ANOVA). The analysis showed that the treatments had a significant effect (P<0.05) on lactic acid content, pH, and Fleigh value (FV), but did not have a sig- nificant effect (P>0.05) on dry matter loss. Treatment P2 produced fermented rice bran with the highest lactic acid content (38.133), the lowest pH (4.327), and the highest FV (33.513) compared to other treatments. In conclusion, treatment P2 resulted in the best-fermented rice bran.